(untitled) (Geography and Tourism, 2019)
Teaching soil science as a part of geography subject is crucial, because students learn not only about soil properties, but also about conscious and rational use of the soil resources. Nowadays digital media play increasingly important role in education and can be employed both in geography classes and soil science. The article aims at comparing various multimedia tools used as a support in teaching on soil science and evaluation of trends concerning the use of these methods in education. The use of ICT during lessons should be purposeful, therefore a need arises to develop strategies on effective use of multimedia and methodological guidance in specific teaching situations. Social media and virtual reality games have changed the way young people perceive the real world, and this includes education. Thus, it is of value to attempt employing role-playing and elements of gamification in teaching soil science and geography lessons.